Local dynamics of a randomly pinned crack front: a numerical study - Gjerden, Knut S.; Stormo, Arne; Hansen, Alex (Frontiers in Physics, 2014)
We investigate numerically the dynamics of crack propagation along a weak plane using a model consisting of fibers connecting a soft and a hard clamp. This bottom-up model has previously been shown to contain the competition of two crack propagation mechanisms: coalescence of damage with the front on small scales and pinned elastic line motion on large scales. We investigate the dynamical scaling properties of the model, both on small and large scale. The model results compare favorable with experimental results on stable crack propagation between sintered PMMA plates.